Simple storage of sperm cells using combination of coconut and glycerol water towards motility and viability of Koi sperm (Cyprinus carpio) - Agista Tsani Untsa; Ganjar Adhywirawan Sutarjo; Riza Rahman Hakim (IJOTA (Indonesian Journal of Tropical Aquatic), 2019)
Fish sperm is a crucial part of fish reproduction, especially for Cyprinus carpio. This study aimed to determine the effect of coconut water and glycerol on the motility and viability of sperm koi fish (Cyprinus carpio) and the best treatment on sperm storage of Showa koi fish.This research was conducted for 45 days at Installation ofPunten Freshwater Cultivation - Malang. Thecompletely randomized design (CRD) used with five treatments and three replications. The treatment comes in 750µl coconut water, 500µl coconut water, and 250µl glycerol, 375µl coconut water, and 375µl glycerol, 250µl coconut water and 500µl glycerol, and 750µl glycerol (P1, P2, P3, P4, and P5, respectively). Briefly, the spermis stored at a low temperature (4℃). Observation of sperm motility used sperm cell dilution contained physiologicalNaCl, while the viability calculation used eosin 2% by the smear method. Motility and viability investigationwere employedwere carried out under a microscope with 400x magnification. The results revealed that the addition of coconut water and glycerol had a significant difference on the motility and viability of sperm koi fish.  It could survive 96 hours of storage, but the longer motility and viability would decrease. The P3 showed the best result compared to others. The P3 had an average motility scale of 96 - 5.00 and the average viability is 87.38%. Based on it, the treatment could increase the motility and viability of koi fish sperm.